Mechanism and influence factors of chromium(VI) removal by sulfide-modified nanoscale zerovalent iron. (June 2019) - Lv, Dan; Zhou, Jiasheng; Cao, Zhen; Xu, Jiang; Liu, Yuanli; Li, Yizhou; Yang, Kunlun; Lou, Zimo; Lou, Liping; Xu, Xinhua
Abstract: Sulfidation of nanoscale zerovalent iron (nZVI) has attracted increasing interest for improving the reactivity and selectivity of nZVI towards various contaminants, such as aqueous Cr(VI) removal. However, the benefits derived from sulfide modification that govern the removal of Cr(VI) remains unclear, which was studied in this work. S-nZVI with higher S/Fe molar ratio showed higher surface area, the discrepancy between the surface-area-normalized removal capacity of Cr(VI) by S-nZVI with different S/Fe indicated that the removal of Cr(VI) was also affected by other factors, such as electron transfer ability, surface-bounded Fe(II) species, and surface charges. High specific surface area would provide more active site for Cr(VI) removal, and as an efficient electron conductor, acicular-like FeSx phase would also favor electron transfer from Fe 0 core to Cr(VI). Low initial pH also enhanced the Cr(VI) removal, and the Cr(VI) removal capacity by S-nZVI and nZVI was not affected by aging process, these results confirmed that the Fe(II) species also played an important role in the Cr(VI) removal. Other influence factors were also investigated for potential application, including temperature, initial Cr(VI) concentration, ionic strength, and co-existed ions. The removal mechanism of Cr(VI) by S-nZVI involved the sulfide modification to increase the specific surface area and provide more active sites, the corrosion of Fe 0 to produce surface-bounded Fe(II) species to adsorb Cr(VI) species, followed by the favored reduction of Cr(VI) to Cr(III) due to the electron transfer ability of FeSx, then the formation of Cr(III)/Fe(III) hydroxides precipitates. Graphical abstract: Image 1 Highlights: S-nZVI showed better reactivity than pristine nZVI towards Cr(VI). S/Fe molar ratio had significant effects on the reactivity of S-nZVI. Cr(VI) was removed through adsorption, reduction, and co-precipitation. FeSx on S-nZVI facilitated the electron transfer and acted as reducing agent. S-nZVI maintained high Cr(VI) removal efficiency after aged 12 days.